Do we know enough? A quality assessment of the Finnish intervention to prevent obstetric anal sphincter injuries. (1st November 2016) - Skriver-Møller, Anne-Cathrine; Madsen, Mia Lund; Poulsen, Mette Østergaard; Overgaard, Charlotte
Abstract: Objective : Especially in the Nordic countries, increases in obstetric anal sphincter injuries (OASIS) have prompted standard use of the Finnish intervention for their prevention. We performed a quality assessment of the introduction of the intervention in a Danish hospital setting. Methods : All vaginal deliveries by primiparous women the year before ( N  = 343) and after ( N  = 334) the introduction were compared in a retrospective, observational design. Fisher's exact test, Student's t -test, and multiple logistic regression analysis were performed. Results : No significant difference in OASIS (OR: 0.5; 95% CI: 0.3–1.1) was found. The post-implementation group saw a significant increase in episiotomy (OR: 1.8; 95% CI: 1.1–2.9) and the length of second stage labor ( p  < 0.05) while intact perineum (OR: 0.5; 95% CI: 0.3–0.9), use of upright positions for birth (OR: 3.2; 95% CI: 1.8–5.5), and neonatal blood gas levels were significantly reduced ( p  < 0.05). Conclusions : Introduction of the Finnish intervention was not followed by a significant reduction of OASIS, but a downward trend was seen. The study results raise questions about potential side effects of the Finnish intervention on neonatal outcomes, intact perineum, and women's free choice of birth positions. More knowledge on effect and side effects from high-evidence studies are needed.